1979
DOI: 10.1111/j.1365-2141.1979.tb03766.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Intracellular pH within Individual Populations of SS and AA Erythrocytes

Abstract: Individual populations of AA and SS erythrocytes were fractionated according to cell density by centrifugation, and the fractions analysed for intracellular pH (PHi), the mole ratio of 2,3-diphosphoglycerate to haemoglobin (DPG:Hb), and cell concentration of haemoglobin (MCHC). The pHi of SS erythrocytes was consistently lower than that of AA erythrocytes throughout the density range, and the lowest pHi of both cell types (AA and SS) was found in cells with the highest density. As the highest density AA and SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Although most of our experiments were carried out in pH 6.8 buffer, pentacoordinate HbS-NO was found to also dominate in all pH 7.2 Trizma buffer (78% pentacoordinate ␣-nitrosyl after 1 h of incubation at 37°C). The pH (6.8) used in most of our experiments is not as subphysiological as one may think since the pH in the sickle red cell has been found to be 7.1-7.2 (42,43). Most importantly, the pentacoordinate HbS-NO species has been shown to predominate in venous blood (40).…”
Section: Discussionmentioning
confidence: 96%
“…Although most of our experiments were carried out in pH 6.8 buffer, pentacoordinate HbS-NO was found to also dominate in all pH 7.2 Trizma buffer (78% pentacoordinate ␣-nitrosyl after 1 h of incubation at 37°C). The pH (6.8) used in most of our experiments is not as subphysiological as one may think since the pH in the sickle red cell has been found to be 7.1-7.2 (42,43). Most importantly, the pentacoordinate HbS-NO species has been shown to predominate in venous blood (40).…”
Section: Discussionmentioning
confidence: 96%
“…Earlier measurements (Seakins, Gibbs, Milner & Bertles, 1973;Kaperonis, Bertles & Chien, 1979) of RBC 2,3-DPG in 'top, middle and bottom' thirds of centrifuged columns of SS and AA cells density fractions, indicated that the increase in the total RBC 2,3-DPG: haemoglobin ratio in the SS cells could be attributed to the-upper and middle fractions. The bottom third of SS red cells showed a low normal 2,3-DPG: haemoglobin ratio.…”
Section: Measurements Of 23-diphosphoglycerate Concentrations In Denmentioning
confidence: 99%
“…Separation of Sickle Cells by Density-Sickle cells are heterogeneous with respect to total magnesium, DPG content, and pH (39,40), which vary with cell density as the cell sickles, therefore we separated sickle cells into three fractions using a discontinuous arabinogalactose density gradient before analysis, thereby allowing comparison with unfractionated whole sickle blood. Cells were fractionated on discontinuous density gradients of Stractan II (arabinogalactan) as described previously (41) with minor modifications (42).…”
mentioning
confidence: 99%